A heat-treatable high FN duplex stainless steel welding rod
By using a specific formula of pill skin to wrap the welding core in the E2209 duplex stainless steel electrode, the flowability and arc stability of the weld are adjusted, and the ferrite transformation after welding is solved, and the mechanical properties and welding quality of the weld are improved. .
Patent Information
- Application Number
- CN202411464913.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-21
AI Technical Summary
After welding of E2209 duplex stainless steel electrode, the weld needs heat treatment to remove residual stress, but after heat treatment, the ferrite in the weld becomes austenite, making it difficult to reach 40-60%, thereby reducing the comprehensiveness of the weld. Mechanical properties.
A high-FN duplex stainless steel welding rod formula that can be heat treated includes welding core and medicine skin of specific components. The medicine skin is evenly wrapped on the outer surface of the welding core through a press coating device. The medicine skin ingredients contain rutile powder and mica powder. Sodium silicate, fluoride, feldspar, chromium powder, molybdenum iron alloy powder, etc., use potassium-sodium water glass as the binder to adjust the flowability and arc stability of the welds and reduce the transformation from ferrite to austenite.
The ferrite content in the weld is improved, the mechanical properties and corrosion resistance of the weld are enhanced, the beautiful molding of the weld is prevented, the pore defects are prevented, and the welding process and the manufacturing performance of the welding rod are improved.
Smart Images

Figure CN118951487B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of duplex stainless steel welding rods, and in particular to a heat-treatable high FN duplex stainless steel welding rod. Background Art
[0002] E2209 duplex stainless steel welding rods usually do not need to be preheated before welding, nor do they require heat treatment after welding. However, when E2209 duplex stainless steel welding rods are used for welding certain large-sized thick-walled parts, heat treatment is often required to eliminate residual stress.
[0003] After the weld deposited metal formed by E2209 duplex stainless steel electrode welding is subjected to high temperature heat treatment to remove residual stress, the residual stress in the weld deposited metal is completely released, which can significantly reduce the risk of cracking of the weld in the service environment. Although the heat treatment removes the residual stress, the problem that follows is that the ferrite content in the weld deposited metal after heat treatment is reduced, and about 10-20% of the ferrite in the weld deposited metal is transformed into austenite. Therefore, the ferrite content in the weld deposited metal is difficult to reach 40-60%, which will significantly reduce the comprehensive mechanical properties of the weld. Summary of the invention
[0004] The problem in the prior art is that after the E2209 duplex stainless steel electrode is used to weld large-sized thick-walled parts, the weld needs to be heat treated. After the weld is heat treated, the ferrite part in the deposited metal will be transformed into austenite, and the ferrite content is difficult to reach 40-60%. In view of the above problems, the present invention provides a heat-treatable high FN duplex stainless steel electrode formula, which includes a welding core and a coating, the diameter of the welding core is 4.0±0.1mm, the thickness of the coating is 2.75±0.1mm, and the coating accounts for 40±5% of the total weight of the welding rod. The welding core, in terms of weight percentage, includes the following elemental components:
[0005] C≤0.03%;
[0006] Si≤0.60%
[0007] Mn≤1.80%
[0008] S≤0.008%
[0009] P≤0.015%
[0010] Cr 19%-22%
[0011] Ni 9%-11%
[0012] Fe balance and unavoidable impurities;
[0013] The coating comprises the following components in parts by weight:
[0014] 18-32 parts of rutile powder;
[0015] 1-5 parts of mica powder;
[0016] 2-4 parts of sodium silicate;
[0017] 1-4 parts of manganese powder;
[0018] Fluoride 2-5 parts;
[0019] Feldspar 6-20 parts;
[0020] 10-16 parts of carbonate;
[0021] 19-25 parts of chromium powder;
[0022] 7-15 parts of ferromolybdenum alloy powder;
[0023] 1-5 parts of ferrochrome nitride powder;
[0024] 1-6 parts of titanium dioxide;
[0025] 1-4 parts of sodium alginate;
[0026] The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7;
[0027] The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1;
[0028] The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60-65:35-40.
[0029] Preferably, the welding core is 308L stainless steel, the grade is S30803.
[0030] Preferably, the preparation method of the heat-treatable high FN duplex stainless steel welding rod comprises the following steps:
[0031] (1) According to the formula, the coating components and the binder are mixed evenly to obtain a mixture of drug powder and binder. The amount of binder added is 18±0.5% of the total mass of the coating;
[0032] (2) The mixture of powder and binder is compounded with the welding core by a pressure coating device at a pressure of 10-15Mpa, so that the coating is evenly wrapped on the outer surface of the welding core.
[0033] Preferably, the binder is potassium sodium water glass.
[0034] The present invention has the following beneficial effects:
[0035] (1) The fluoride in the coating component of the present invention is a slag-forming agent, which can adjust the melting point of the slag, adjust the fluidity of the weld metal, reduce the surface tension of the liquid metal, help the gas in the weld to escape quickly, make the weld shape beautiful, and prevent the formation of pore defects in the weld;
[0036] (2) The rutile in the coating composition of the present invention can stabilize the welding arc, calm the molten pool, refine the transition droplets, beautify the weld formation, and ensure the slag coverage, but excessive use can easily reduce the mechanical properties;
[0037] (3) The mica powder in the coating composition of the present invention has the function of improving arc stability, reducing spatter, and improving the manufacturing performance of the welding rod;
[0038] (4) The sodium silicate in the coating composition of the present invention has the function of stabilizing the arc and improving the welding processability;
[0039] (5) The electrolytic manganese in the coating composition of the present invention acts as a transition element to the deposited metal and can effectively remove oxygen from the weld, thereby improving the purity and mechanical properties of the weld.
[0040] (6) The feldspar in the coating composition of the present invention has the functions of stabilizing the arc, controlling the weld morphology, promoting the formation of the molten pool and facilitating the slag removal of the weld. However, excessive feldspar will slow down the welding speed and increase the viscosity of the slag, thereby affecting the welding efficiency and quality.
[0041] (7) In the coating composition of the present invention, marble is not added, but lithium carbonate and strontium carbonate are additionally added. The addition of lithium carbonate and strontium carbonate changes the heat transfer characteristics of the slag, affects the cooling process of the weld, makes the cooling process faster, inhibits the transformation of ferrite to austenite, and increases the ferrite content in the deposited metal;
[0042] (8) The chromium powder and molybdenum-iron alloy powder in the coating composition of the present invention are used to improve the corrosion resistance and strength of the weld;
[0043] (9) The nitrogen element in the coating composition of the present invention serves to improve the strength, corrosion resistance and high temperature performance of the weld;
[0044] (10) The titanium dioxide in the coating component of the present invention can increase the plasticity of the electrode coating and is a slag-forming agent component;
[0045] (11) The sodium alginate in the coating component of the present invention has the function of improving the stability of the welding arc and the welding processability;
[0046] (12) The binder of the present invention is potassium sodium water glass, which can play a role in stabilizing the arc;
[0047] (13) In order to increase the content of ferrite in the deposited metal, the present invention increases the content of Cr and Mo metal elements in the deposited metal. The increase of Cr and Mo metal elements is not conducive to the formation of austenite during the heat treatment process. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 : Microstructure image of the weld obtained after welding with the heat-treatable high FN duplex stainless steel electrode obtained in Example 1, magnified 100 times.
[0049] Figure 2 : Microstructure image of the weld obtained after welding with the heat-treatable high FN duplex stainless steel electrode obtained in Example 2, magnified 100 times. DETAILED DESCRIPTION
[0050] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0051] The grade of ferrochromium nitride in the following examples of the present invention is FeNCr3-B.
[0052] The welding core in the following embodiments of the present invention is made of 308L stainless steel, with the grade S30803.
[0053] Example 1
[0054] A heat-treatable high FN duplex stainless steel welding rod consists of a welding core and a coating, wherein the diameter of the welding core is 4.0 mm, the thickness of the coating is 2.75 mm, and the coating accounts for 40% of the total weight of the welding rod.
[0055] The coating has the following components by weight:
[0056] 32 parts of rutile powder;
[0057] 5 parts of mica powder;
[0058] 4 parts of sodium silicate;
[0059] 4 parts of manganese powder;
[0060] 5 parts of fluoride;
[0061] Feldspar 20 parts;
[0062] 16 parts of carbonate;
[0063] 25 parts of chromium powder;
[0064] 15 parts of ferromolybdenum alloy powder;
[0065] 5 parts of ferrochrome nitride powder;
[0066] 6 parts of titanium dioxide;
[0067] 4 parts of sodium alginate;
[0068] The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7;
[0069] The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1;
[0070] The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60:40.
[0071] The heat-treatable high FN duplex stainless steel welding rod is prepared as follows:
[0072] (1) According to the formula, the coating components and the binder are mixed evenly to obtain a mixture of drug powder and binder. The amount of binder added is 18% of the total weight of the coating;
[0073] (2) The mixture of powder and binder is compounded with the welding core by a pressure coating device at a pressure of 10 MPa, so that the coating is evenly wrapped on the outer surface of the welding core.
[0074] The microstructure image of the weld obtained after welding with the high FN duplex stainless steel electrode obtained in Example 1 after magnification 100 times is shown in the attached manual. Figure 1 As shown in the figure, it can be seen that the weld is an austenite plus dendrite ferrite structure. Example 2
[0075] A heat-treatable high FN duplex stainless steel welding rod consists of a welding core and a coating, wherein the diameter of the welding core is 4.0 mm, the thickness of the coating is 2.75 mm, and the coating accounts for 40% of the total weight of the welding rod.
[0076] The coating has the following components by weight:
[0077] 30 parts of rutile powder;
[0078] 3 parts of mica powder;
[0079] 3 parts of sodium silicate;
[0080] 3 parts of manganese powder;
[0081] 4 parts of fluoride;
[0082] Feldspar 15 parts;
[0083] 14 parts of carbonate;
[0084] 24 parts of chromium powder;
[0085] 14 parts of ferromolybdenum alloy powder;
[0086] 4 parts of ferrochrome nitride powder;
[0087] 5 parts of titanium dioxide;
[0088] 3 parts of sodium alginate;
[0089] The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7;
[0090] The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1;
[0091] The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60:40.
[0092] The heat-treatable high FN duplex stainless steel welding rod is prepared as follows:
[0093] 1) According to the formula, the coating components and the binder are mixed evenly to obtain a mixture of drug powder and binder. The amount of binder added is 18% of the total weight of the coating;
[0094] (2) The mixture of powder and binder is compounded with the welding core by a pressure coating device at a pressure of 10 MPa, so that the coating is evenly wrapped on the outer surface of the welding core.
[0095] The microstructure image of the weld obtained after welding with the high FN duplex stainless steel electrode obtained in Example 2 after magnification 100 times is shown in the attached manual. Figure 2 As shown in the figure, it can be seen that the weld is an austenite plus dendrite ferrite structure.
[0096] Example 3
[0097] A heat-treatable high FN duplex stainless steel welding rod consists of a welding core and a coating, wherein the diameter of the welding core is 4.0 mm, the thickness of the coating is 2.75 mm, and the coating accounts for 40% of the total weight of the welding rod.
[0098] The coating has the following components by weight:
[0099] 30 parts of rutile powder;
[0100] 3 parts of mica powder;
[0101] 3 parts of sodium silicate;
[0102] 3 parts of manganese powder;
[0103] 4 parts of fluoride;
[0104] Feldspar 15 parts;
[0105] 13 parts of carbonate;
[0106] 23 parts of chromium powder;
[0107] 12 parts of ferromolybdenum alloy powder;
[0108] 3 parts of ferrochrome nitride powder;
[0109] 3 parts of titanium dioxide;
[0110] 3 parts of sodium alginate;
[0111] The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7;
[0112] The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1;
[0113] The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60:40.
[0114] The heat-treatable high FN duplex stainless steel welding rod is prepared as follows:
[0115] (1) According to the formula, the coating components and the binder are mixed evenly to obtain a coating viscous liquid, and the amount of the binder added is 18% of the total weight of the coating; the binder is potassium sodium water glass
[0116] (2) The coating viscous liquid is compounded with the welding core under a pressure of 10 MPa through a pressure coating device so that the coating is evenly wrapped on the outer surface of the welding core.
[0117] Example 4
[0118] A heat-treatable high FN duplex stainless steel welding rod consists of a welding core and a coating, wherein the diameter of the welding core is 4.0 mm, the thickness of the coating is 2.75 mm, and the coating accounts for 40% of the total weight of the welding rod.
[0119] The coating has the following components by weight:
[0120] 25 parts of rutile powder;
[0121] 2 parts of mica powder;
[0122] 3 parts of sodium silicate;
[0123] 2 parts of manganese powder;
[0124] 3 parts of fluoride;
[0125] Feldspar 10 parts;
[0126] 12 parts of carbonate;
[0127] 20 parts of chromium powder;
[0128] 10 parts of ferromolybdenum alloy powder;
[0129] 2 parts of ferrochrome nitride powder;
[0130] 2 parts of titanium dioxide;
[0131] 2 parts of sodium alginate;
[0132] The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7;
[0133] The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1;
[0134] The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60:40.
[0135] The heat-treatable high FN duplex stainless steel welding rod is prepared as follows:
[0136] (1) According to the formula, the coating components and the binder are mixed evenly to obtain a coating viscous liquid, and the amount of the binder added is 18% of the total weight of the coating; the binder is potassium sodium water glass
[0137] (2) The coating viscous liquid is compounded with the welding core under a pressure of 10 MPa through a pressure coating device so that the coating is evenly wrapped on the outer surface of the welding core.
[0138] Example 5
[0139] A heat-treatable high FN duplex stainless steel welding rod consists of a welding core and a coating, wherein the diameter of the welding core is 4.0 mm, the thickness of the coating is 2.75 mm, and the coating accounts for 40% of the total weight of the welding rod.
[0140] The coating has the following components by weight:
[0141] 18 parts of rutile powder;
[0142] 1 part mica powder;
[0143] 2 parts of sodium silicate;
[0144] 1 part manganese powder;
[0145] 2 parts of fluoride;
[0146] 6 parts of feldspar;
[0147] 10 parts of carbonate;
[0148] 19 parts of chromium powder;
[0149] 7 parts of ferromolybdenum alloy powder;
[0150] 1 part of ferrochrome nitride powder;
[0151] 1 part of titanium dioxide;
[0152] 1 part of sodium alginate;
[0153] The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7;
[0154] The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1;
[0155] The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60:40.
[0156] The heat-treatable high FN duplex stainless steel welding rod is prepared as follows:
[0157] (1) According to the formula, the coating components and the binder are mixed evenly to obtain a coating viscous liquid, and the amount of the binder added is 18% of the total weight of the coating; the binder is potassium sodium water glass
[0158] (2) The coating viscous liquid is compounded with the welding core under a pressure of 10 MPa through a pressure coating device so that the coating is evenly wrapped on the outer surface of the welding core.
[0159] Comparative Example 1 is the same as Example 1, except that the weight proportion of chromium powder in the coating of Comparative Example 1 is 15 parts.
[0160] Comparative Example 2 is the same as Example 1, except that, in Comparative Example 2, no molybdenum-iron alloy powder is added to the medicinal skin component, and molybdenum powder and iron powder are additionally added, with the weight proportion of the molybdenum powder added being 5 parts and the weight proportion of the iron powder added being 6 parts.
[0161] Comparative Example 3 is the same as Example 1, except that strontium carbonate and lithium carbonate are not added in Comparative Example 3, and marble is additionally added, and the weight portion of the marble added is 16 parts.
[0162] Comparative Example 4 is the same as Example 1, except that lithium carbonate is not added in Comparative Example 4, and the weight portion of strontium carbonate added is 16 parts.
[0163] Comparative Example 5 is the same as Example 1, except that no strontium carbonate is added in Comparative Example 5, and the weight portion of lithium carbonate added is 16 parts.
[0164] Comparative Example 6 is the same as Example 1, except that the total weight parts of strontium carbonate and lithium carbonate added in Comparative Example 6 is 5 parts.
[0165] Comparative Example 7 is the same as Example 1, except that the carbonate in Comparative Example 7 consists of strontium carbonate and lithium carbonate in a mass ratio of 1:1.
[0166] Comparative Example 8 is the same as Example 1, except that the carbonate in Comparative Example 8 consists of strontium carbonate, calcium carbonate and lithium carbonate in a mass ratio of 2:6:1.
[0167] Comparative Example 9 is the same as Example 1, except that the carbonate in Comparative Example 9 consists of strontium carbonate and calcium carbonate in a mass ratio of 3:7.
[0168] Comparative Example 10 is the same as Example 1, except that the carbonate in Comparative Example 10 consists of calcium carbonate and lithium carbonate in a mass ratio of 3:7.
[0169] Performance Testing
[0170] The welding rods obtained in Examples 1-6 of the present invention, Comparative Examples 1-10, and the E2209 heat-treatable high FN duplex stainless steel welding rod were respectively subjected to surfacing welding, with the number of surfacing layers being 3 layers. The intermediate metal deposited layer was taken for elemental composition analysis and comparison. The analysis and comparison results are shown in Table 1.
[0171] The process parameters of cladding welding are as follows:
[0172] Welding current: 160A.
[0173] Table 1
[0174] ,
[0175] E2209 in Table 1 is a duplex stainless steel electrode.
[0176] The deposited metals obtained in Examples 1-5 of the present invention and Comparative Examples 1-10 were subjected to post-weld heat treatment at a temperature of 690° C. for 8 h. The ferrite content of the intermediate metal deposited layer was analyzed and compared. The results of the analysis and comparison are shown in Table 2.
[0177] Table 2
[0178] ,
[0179] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A heat-treatable high FN duplex stainless steel welding rod, characterized in that: The welding rod comprises a welding core and a coating, wherein the diameter of the welding core is 4.0±0.1 mm, the thickness of the coating is 2.75±0.1 mm, and the coating accounts for 40±5% of the total weight of the welding rod; The welding core comprises the following elements in terms of weight percentage: C≤0.03%; Si≤0.60% Mn≤1.80% S≤0.008% P≤0.015% Cr 19%-22% Ni 9%-11% Fe balance and unavoidable impurities; The coating comprises the following components in parts by weight: 18-32 parts of rutile powder; 1-5 parts of mica powder; 2-4 parts of sodium silicate; 1-4 parts of manganese powder; Fluoride 2-5 parts; Feldspar 6-20 parts; 10-16 parts of carbonate; 19-25 parts of chromium powder; 7-15 parts of ferromolybdenum alloy powder; 1-5 parts of ferrochrome nitride powder; 1-6 parts of titanium dioxide; 1-4 parts of sodium alginate; The carbonate is composed of strontium carbonate and lithium carbonate in a mass ratio of 3:7; The fluoride is a mixture of sodium fluoride, calcium fluoride and barium fluoride in a mass ratio of 1:2:1; The mass ratio of molybdenum to iron in molybdenum-iron alloy is 60-65:35-40.
2. A heat-treatable high FN duplex stainless steel welding rod according to claim 1, characterized in that: The welding core is 308L stainless steel, and the grade is S30803.
3. A heat-treatable high FN duplex stainless steel welding rod according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: (1) According to the formula, the coating components and the binder are mixed evenly to obtain a mixture of drug powder and binder. The amount of binder added is 18±0.5% of the total mass of the coating; (2) The mixture of powder and binder is compounded with the welding core by a pressure coating device at a pressure of 10-15Mpa, so that the coating is evenly wrapped on the outer surface of the welding core.
4. A heat-treatable high FN duplex stainless steel welding rod according to claim 3, characterized in that: The binder is potassium sodium water glass.
Citation Information
Patent Citations
Acidic coating super two-phase stainless steel electrode
CN101323058A
Two-phase stainless steel electrode
CN102233489A
Acid red skin stainless steel welding rod with high crack resistance and high porosity resistance
CN110842394A
Low hydrogen type covered electrode for penetration welding
JP1993212586A
Coated electrode for duplex stainless steel welding for pulverizing solidified crystalline particle
JP2010234429A
